Corporate Management: A Comparison of Chinese (Global Journal of Management and Business Research, 2021)
Digitalization has increased awareness of the students. Access of Clients to the data and information has also improved in the era of transformative marketing. Because of these developments, Corporate Management of every firm is always struggling to differentiate themselves from revelries. Two neighbors in Asia China and India are continually positioning themselves in the market to show themselves as leaders in corporate world. Corporate Managements are continually looking for a competitive edge.
Keywords: corporate brand equity; brand awareness; brand loyalty; perceived quality; china